#‏al_Aqsa_Is_In_Danger‬: The digital gatekeepers of al-Aqsa mosque - de vries, Maya; Alyan, Eman; Kligler-Vilenchik, Neta; Ma’oz, Moshe; Maoz, Ifat (AoIR Selected Papers of Internet Research, 2016)
One of the most religiously and nationally contested sites in the asymmetrical conflict between Israelis and Palestinians is al-Aqsa Mosque (Temple Mount) . It is a key site and symbol that can mobilize local Palestinian resistance (Pullan, 2014: 168). The current study explores the ways in which social media platforms are being used by East Jerusalem Palestinians to mobilize religious practices and political activism over this site. Palestinians from East Jerusalem are isolated by geo-political barriers from other Palestinian communities in the West Bank and the Gaza Strip, and live under Israeli control (Cohen, 2007). Within this political context, we examine two Facebook pages: I am from Jerusalem (انا من القدس) and Jerusalem City (مدينة القدس); both are administered by Palestinians from East Jerusalem and focus on al-Aqsa Mosque. The dataset that includes 120 posts and 262 comments has been collected during the month of August 2014 and was qualitatively analyzed.